Gender gaps in landownership across and within households in four Asian countries - Kieran, C; Sproule, K; Quisumbing, AR; Doss, CR (University of Wisconsin Press, 2017)
Using nationally representative data from Bangladesh, Tajikistan, Timor-Leste, and Vietnam, this paper investigates which individual and household characteristics influence men’s and women’s landownership across and within households. Often neglected in household-level statistics, married women in all countries are landowners. Across different household structures, women own less land than men, and less land relative to the household average as household landholdings increase. Increasing gender inequality with household wealth cannot be consistently explained by an increasing share of household land devoted to crops. Findings support the need to strengthen women’s land rights within marriage and to protect them should the marriage dissolve.